Edukasi Pengelolaan Sampah Rumah Tangga Bagi Pendidkan Anak Usia Dini - Zulfiar, Muhammad Heri; Nurjanah, Adhianty; Azhar, Muhammad; Ritonga, Mukail (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Waste is a complex and integrated problem at the upstream, service, and downstream levels. Each stage has different problems despite being inseparable. The problem is that the volume of waste reaches 100 fleets per day, carrying a supply of approximately 600 tons of waste. There is limited land for waste disposal in Yogyakarta, and the main access is a disposal route that causes air and water pollution, not to mention the problem of handling waste at landfills in terms of technical or technological. Households as waste producers (upstream), it is time not only to supply waste, but from this stage, the waste begins to be managed so that it does not accumulate in landfills. One of these efforts is the need for social engineering to change societal behavior. This mentoring activity in Serut Hamlet, Palbapang, is a miniature in handling changes in community behavior to become aware of waste. The service aims to provide awareness and understanding in managing household waste (upstream) through education. The method was to create collaboration between local institutions, specifically the Azola Waste Bank group representing waste activists with Early Childhood Education so that they can be synergistic and collaborative in changing community behavior through roles and examples among parents of students. These activities start from the stage of sorting waste from the kitchen. Then, the waste is taken to the school and collected by the waste bank, teaching the technological transformation of the use and processing of waste recycling for parents and bringing up an SPS PAUD curriculum about waste. The activity results show that public awareness and understanding of household waste management have been built. The activity patterns can provide education to students.